Safety and efficacy of toll-like receptor agonists as therapeutic agents and vaccine adjuvants for infectious diseases in animals: a systematic review - Oboge, Harriet; Riitho, Victor; Nyamai, Mutono; Omondi, George P.; Lacasta, Anna; Githaka, Naftaly; Nene, Vishvanath; Aboge, Gabriel; Thumbi, S. M. (Frontiers in Veterinary Science, 2024)
IntroductionStrengthening global health security relies on adequate protection against infectious diseases through vaccination and treatment. Toll-like receptor (TLR) agonists exhibit properties that can enhance immune responses, making them potential therapeutic agents or vaccine adjuvants.MethodsWe conducted an extensive systematic review to assess the efficacy of TLR agonists as therapeutic agents or vaccine adjuvants for infectious diseases and their safety profile in animals, excluding rodents and cold-blooded animals. We collected qualitative and available quantitative data on the efficacy and safety outcomes of TLR agonists and employed descriptive analysis to summarize the outcomes.ResultsAmong 653 screened studies, 51 met the inclusion criteria. In this review, 82% (42/51) of the studies used TLR agonists as adjuvants, while 18% (9/51) applied TLR agonist as therapeutic agents. The predominant TLR agonists utilized in animals against infectious diseases was CpG ODN, acting as a TLR9 agonist in mammals, and TLR21 agonists in chickens. In 90% (46/51) of the studies, TLR agonists were found effective in stimulating specific and robust humoral and cellular immune responses, thereby enhancing the efficacy of vaccines or therapeutics against infectious diseases in animals. Safety outcomes were assessed in 8% (4/51) of the studies, with one reporting adverse effects.DiscussionAlthough TLR agonists are efficacious in enhancing immune responses and the protective efficacy of vaccines or therapeutic agents against infectious diseases in animals, a thorough evaluation of their safety is imperative to in-form future clinical applications in animal studies.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=323122.